Stories from the frontlines: decolonising social contracts for disasters. (16th August 2018) - Siddiqi, Ayesha; Canuday, Jose Jowel P.
Abstract : Disasters are framed as political moments when states are unable to provide security to their citizens, causing disruption and a possible 'break' in the state—citizen social contract. Evidence from the frontlines of insurgency and secessionist movements in southern Philippines suggests that social contracts do not 'break' in this manner, despite widespread suffering during a complex event. This paper presents new perspectives on social contracts after disasters, in conflict‐affected regions. Using ethnographic data from two case studies in the Philippines, it argues that disasters in conflict‐affected areas do not manifest a 'break' in social contracts in ways that result in 'state failure' and 'insurgent capture'. Instead, it shows that the state—citizen contract is a dynamic contestation of state responsibilities, while also being malleably resilient. The inequalities and anxieties prevalent in social contracts are reproduced in the highly differentiated experiences of 'disaster citizenship' for people living amidst conflict.